(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Paediatric diarrhoea, the burning issue of nowadays, drastically affects the child mortality and morbidity. Apart from virus and bacteria, parasites also play an important role in causing diarrhoea at that age group. Giardiasis, the most prevalent among the parasitic infections, though neglected yet carries significance because of its long term health issues. The aim of the study was to identify the intestinal parasites by wet mount preparation and further detection of the flagellated protozoan parasite, Giardia by special staining - Trichrome staining technique. Materials and methods: It was an observational cross sectional study which was carried between the periods of July 2019 to June 2020, where a total of 200 diarrhoeic patients up to 18 years were enrolled. Direct microscopic method was done where parasites were detected by wet mount preparation and further Trichrome stainning was performed for the detection of Giardia. Results: Out of 200 faecal samples, cysts of Giardia, ova of Ascaris Lumbricoides (AL) Trichuris Trichiura (TT) and both AL and TT were identified in 2.5%, 1.5%, 0.5% and 1.0% samples respectively by wet mount preparation. By Trichrome staining method we detected 3.5% of Giardia cysts. Conclusion: Staining technique could be applied in addition to wet mount preparation of stool samples. So that we could recover the undetected Giardia cyst in the aforesaid samples. JCMCTA 2021 ; 32 (2) : 111-114